The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s13213-011-0215-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of transgenic Bt176 and non-transgenic corn silage on the structure of rumen bacterial communities

Abstract: The aim of the present study was to investigate the possible effects of a diet containing transgenic corn (Zea mays), cultivar Bt176 expressing the insecticidal protein CryIA(b), on bacterial diversity of the cow rumen in vivo. Silage prepared with Bt176 corn and its parental non-transgenic cultivar showed no significant differences in either composition or in vivo degradability. Four cows were fed for 35 days with the different silage in a cross-over feeding experiment. The overall structure of rumen bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…Similar results have been obtained in cows, where shortterm consumption of GM maize did not affect rumen microbiota as assessed by 16S rRNA gene sequencing (11), quantitative PCR (12), or ribosomal intergenic spacer analysis (30). Culturable amylolytic and cellulolytic bacteria were also unaffected by 3 years of feeding GM maize to sheep (6).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similar results have been obtained in cows, where shortterm consumption of GM maize did not affect rumen microbiota as assessed by 16S rRNA gene sequencing (11), quantitative PCR (12), or ribosomal intergenic spacer analysis (30). Culturable amylolytic and cellulolytic bacteria were also unaffected by 3 years of feeding GM maize to sheep (6).…”
Section: Discussionsupporting
confidence: 75%
“…As the maternal microbiota provides the inoculum for colonization of the offspring digestive tract (19), any effect that GM maize consumption may have on the intestinal microbiota of pregnant sows could affect the health and lifelong performance of their offspring. A number of studies have investigated the impact of Bt maize consumption on the intestinal microbiota of ruminants (11,12,30), and our group has evaluated its influence on the porcine microbiota (13,14). However, results from transgenerational studies are absent from the literature, and, to our knowledge, this is the first study to investigate the effects of GM maize on the intestinal microbiota of pregnant sows and their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Einspanier et al (11) found no effect of 28 days of feeding Bt maize to cows on ruminal bacterial communities using 16S rRNA gene sequencing. Similarly, ribosomal intergenic spacer analysis revealed no effects of feeding Bt 176 maize silage for 35 days on ruminal bacterial population structure in cows (6). Likewise, Trabalza-Marinucci et al (51) reported no effect of feeding Bt maize for 36 months on the ruminal microbiota of sheep, as revealed by culturing.…”
mentioning
confidence: 98%
“…11,12 Transgenic insect-resistant corn and transgenic herbicide-resistant corn are the most extensively cultivated GM corn varieties and have great potential for popularization in China. 1 There have been lots of feeding trials focusing on a safety evaluation of transgenic insect-resistant corn with respect to gut bacteria [13][14][15][16] and a few studoes reported no completely consistent effects on the intestinal bacteria of animals. However, most of the differences were regarded to have no negative effects on animal health.…”
Section: Introductionmentioning
confidence: 99%